Empathy in the Administrative Field of Healthcare: Soft Skills Training and Its Impact on the Patient Experienced Its Impact on the Patient Experiencework. - Baraglia, Alex O. (Revista del Hospital Italiano de Buenos Aires, 2025)
Empathy has been a key factor in human evolution, facilitating cooperation, social cohesion, and a sense of justice. While it has been widely studied in the clinical field, its impact on the performance of administrative staff in healthcare has received less attention. This article looks into the evolutionary development of empathy and its relevance in hospital management, highlighting its influence on patient interactions and organizational dynamics.From an interdisciplinary perspective, the challenges of applying empathy in healthcare administration are analyzed, including the risk of bias and the need for proper emotional regulation. It is argued that training in soft skills, particularly for administrative staff, is essential to improving service quality and strengthening workplace dynamics. Training strategies based on interactive simulations, mentoring, and virtual tools are proposed, allowing administrative personnel to develop balanced empathy that optimizes their performance without compromising objectivity in decision-making.Through a systemic analysis, we suggest that empathy should not be seen as merely an individual skill but as a structural factor influencing the overall functioning of healthcare institutions. Thus, the need for organizational policies that integrate empathy as a core principle in hospital management is emphasized.
Keywords: empathy; evolution; healthcare administrative staff; virtual platform; patient care